2017
DOI: 10.1097/bpo.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

The POSNA-COUR International Scholar Program. Results of the First 7 Years

Abstract: Level IV-case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Eighty-seven percent of participants returned completed surveys. Other programs have reported response rates of 37.5% 5 and 62%, 6 demonstrating the common challenge of collecting information from busy health care providers. Our high response rate may be related not only to the great rapport established between our team and this cohort of physicians but also to their personal and professional satisfaction of reporting on the success of a specific project.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-seven percent of participants returned completed surveys. Other programs have reported response rates of 37.5% 5 and 62%, 6 demonstrating the common challenge of collecting information from busy health care providers. Our high response rate may be related not only to the great rapport established between our team and this cohort of physicians but also to their personal and professional satisfaction of reporting on the success of a specific project.…”
Section: Discussionmentioning
confidence: 99%
“…4 This clinical gap has motivated several bi-directional initiatives such as travel fellowships for foreign orthopaedic surgeons, including Haiti’s only two pediatric orthopaedic surgeons, to participate in specialty-specific conferences in the United States. 23 Another approach in this subspecialty has been to organize outreach courses in resource-challenged environments. 5…”
Section: Discussionmentioning
confidence: 99%
“…There is little literature assessing the benefits that international observerships have on healthcare professionals and trainees coming from LMIC. [15][16][17] Just recently, the ACS evaluated the effect of its international scholarships program for non-U.S. surgeons and found that 80 to 90% of alumni considered it a very positive experience and provided them with further career opportunities that would not have been possible without it. 16 Another study concluded that international rotations in the U.S. offer Mexican medical students extensive benefits in academic and personal development, including cultural competency, knowledge on foreign health systems, sharpening English skills and medical terminology, appreciation of broader interdisciplinary team roles and interactions, improvement of students' self-efficacy, and, expanding their global health perspective.…”
Section: Discussionmentioning
confidence: 99%
“…17 The present survey adds further evidence of the positive impact that U.S. observership have on health professionals coming from LMIC. [15][16][17] It also highlights the role that international societies such as the PTS can play in providing an essential platform for educational opportunities and reciprocal exchanges. This is significantly facilitated via the partnership of PTS with a major academic institution like VCU dedicated to education, research, and innovation and serving as a comprehensive Level 1 trauma center.…”
Section: Discussionmentioning
confidence: 99%